Effect of Work Life Balance and Job Satisfaction on Organizational Commitment at PT Jatim Auto Comp Indonesia (JAI) - Afrinianto, Rifqi Mayrenanda Alif; Ambarwati, Titiek; Novianti, Khusnul Rofida (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to examine the effect of work life balance and job satisfaction on organizational commitment. This research was conducted on employees at PT Jatim Auto Comp Indonesia (JAI) which is engaged in wiring harness manufacturing. The sampling technique used total sampling with a total sample of 55 employees. The type of data used in this research is primary data in the form of a questionnaire. The data analysis technique carried out in this study used quantitative methods so that the data in the form of numbers was processed using multiple linear regression analysis methods. The results of the scale range in this study indicate that work-life balance is in the high category. Job satisfaction is included in the satisfied category. Organizational commitment is included in the high category. The results showed that work life balance has a positive effect on organizational commitment. Job satisfaction has a positive effect on organizational commitment. Work-life balance and job satisfaction have a positive effect on organizational commitment. Job satisfaction has the most influence on organizational commitment.